Communication Features of Sustainable Fashion on Instagram: Use of the Hashtag #sustainablefashion - Telyčėnaitė, Austė (Information & Media, 2023)
Scientific research indicates that perceptions of sustainable fashion are diverse and influenced by regional, cultural, and industry-specific attitudes and behaviours. Recent studies highlight the growing impact of social media on individual knowledge, attitudes, and behaviours, particularly Instagram’s role in promoting sustainable fashion values and encouraging appropriate consumer behaviour. The article presents a study aimed at identifying the contexts of sustainable fashion communication on Instagram in Lithuania, highlighting the key actors of the sustainable fashion ecosystem, the subject matter of the communication and the specifics of its presentation. The study found that Instagram in Lithuania is dominated by the concept of sustainable fashion, and the majority of accounts communicating sustainable fashion are commercial entities. The study also revealed that opinion leaders are not actively involved in the communication of sustainable fashion, most accounts using the hashtag have a small number of followers, and the content they publish does not expand on the topic of sustainability, but only mentions it. The posts that do dive deeper into the topic of sustainability show a multifaceted perception of the phenomenon of sustainable fashion and the issues surrounding it, determined by the different perspectives of the actors involved in the communication.
Keywords: sustainability; sustainable fashion; sustainable fashion communication; social media online communities